Pengaruh Faktor Internal Terhadap Profitabilitas Perusahaan Asuransi - Sanputra, Adrian Hartanto Darma; Puspitasari, Cindy Kharisma; Puspita Sari, Citra Duwi; Ramadina, Defrina Eka Orchidta; Jannah, Devita Hidayatul; Aprilia, Ervina Dwi; Salma, Ghina Mufidatus (Jayapangus Press, 2024)
This study explores the internal elements that influence the profitability of life insurance companies in Indonesia, using Resource-Based Theory (RBT). A quantitative exploratory method was used to collect data from conventional and sharia life insurance companies registered with the Financial Services Authority (OJK) during the 2019-2023 period. To select 24 companies that meet the criteria, purposive sampling method is used to collect 120 sample data. According to the Vector Error Correction Model (VECM) analysis, leverage and underwriting risk have a positive effect on profitability in the long run; in contrast, capital volume and firm size have a negative effect. The results suggest that operational efficiency, flexibility in capital management, and determining the ideal firm size are important. Before making an investment, potential investors should thoroughly analyze the company's organization and performance, as well as potential underwriting and leverage risks.